2015
DOI: 10.1111/clr.12544
|View full text |Cite
|
Sign up to set email alerts
|

Radiological comparison of laser‐microtextured and platform‐switched implants in thin mucosal biotype

Abstract: Laser-microtexturing of implant collar or platform-switched implant/abutment connection did not eliminate crestal bone loss, if at the time of implant placement vertical soft tissue thickness was ≤2 mm. However, laser-microtextured implants may present less proximal bone loss than platform-switching implants in the period before implant loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of the titles and abstracts resulted in 22 articles identified as full‐text articles, and seven were excluded for the following reasons: follow‐up <12 months; 44 , 45 redundant studies; 32 LMS design not only in implant neck; 21 , 46 performed with additional surgeries such as hard 47 or soft tissue 48 augmentation. Finally, 15 eligible articles 21‐31,33‐36 were included in this study. The characteristics of the included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles are RCTs 30 , 31 , 33 and six are cohort studies 27‐29,34‐36 . Six case series 21–26 observing implants with LMS collars without controls were also included to evaluate the overall performances of the LMS design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations